2021
DOI: 10.1073/pnas.2022142118
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon blockade restores functional β-cell mass in type 1 diabetic mice and enhances function of human islets

Abstract: We evaluated the potential for a monoclonal antibody antagonist of the glucagon receptor (Ab-4) to maintain glucose homeostasis in type 1 diabetic rodents. We noted durable and sustained improvements in glycemia which persist long after treatment withdrawal. Ab-4 promoted β-cell survival and enhanced the recovery of insulin+ islet mass with concomitant increases in circulating insulin and C peptide. In PANIC-ATTAC mice, an inducible model of β-cell apoptosis which allows for robust assessment of β-cell regener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…Aberrant glucagon production correlates with diabetes. Research shown that blockade of glucagon signaling lowers glycemia in mouse models while enhancing formation of functional β cell mass (51). In our study, plasma glucagon levels significantly decreased in KO-HFD mice compared with WT-HFD group.…”
Section: Discussionsupporting
confidence: 54%
“…Aberrant glucagon production correlates with diabetes. Research shown that blockade of glucagon signaling lowers glycemia in mouse models while enhancing formation of functional β cell mass (51). In our study, plasma glucagon levels significantly decreased in KO-HFD mice compared with WT-HFD group.…”
Section: Discussionsupporting
confidence: 54%
“…Glucagon, mainly produced by alpha-pancreatic cells, although it is an important approach to handle hypoglycemic events, has hardly been considered a protagonist of diabetes physiopathology. On the contrary, Unger RH, for a long time has supported the importance of this hormone for diabetes onset [ 120 , 121 ].…”
Section: Glucagon: Insulin Antidote or Main Driver Of Diabetes Homeostasis?mentioning
confidence: 99%
“…Our previous study, together with others, has proven that GCGR blockage could decrease blood glucose and improve the phenotype of T1D mice. Strikingly, GCGR mAb increased the number of pancreatic β cells and upregulated circulating insulin levels by inducing αto β-cell transdifferentiation in T1D mice [8,11]. However, GCGR mAb substantially increased pancreatic α-cell mass, which brings a safety concern on the α-cell tumor [12].…”
Section: Discussionmentioning
confidence: 99%